THE INFLUENCE OF LIVING HADITH ON COMMERCIAL TRANSACTIONS AMONG BANJAR Z GENERATION IN PALANGKA RAYA - Ahmad, Zakaria; Wakhidah, Nur (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2025)
Technological developments and shifting consumption patterns have significantly influenced the manifestation of living hadith practices among the Banjar community in Palangka Raya, particularly among members of Generation Z. This study investigates how this generation interprets and applies prophetic values within contemporary sale and purchase contracts in a digital environment. Employing a qualitative methodology, data were gathered through interviews, observation, and documentation, and analyzed using thematic analysis. The findings reveal five key transformations: the shift from verbal contracts to general social expressions; from religious dialogue to functional economic acts; from symbolic transaction spaces to digital platforms; the tension between traditional and modern contractual contexts; and the emergence of fragmented symbolic consciousness. This research contributes to the scholarship of living hadith by conceptualizing its transformation within the sphere of contemporary economic practices. Moreover, it offers critical insights into how Islamic ethical values can be maintained and rearticulated in the midst of evolving digital cultures and consumer behavior. [Perkembangan teknologi dan perubahan pola konsumsi telah memengaruhi secara signifikan praktik living hadith di kalangan masyarakat Banjar di Palangka Raya, khususnya pada Generasi Z. Penelitian ini mengkaji bagaimana generasi ini menginterpretasikan dan menerapkan nilai-nilai kenabian dalam praktik akad jual beli di lingkungan digital. Dengan menggunakan pendekatan kualitatif, data dikumpulkan melalui wawancara, observasi, dan dokumentasi, kemudian dianalisis secara tematik. Hasil penelitian mengungkapkan lima transformasi utama: pergeseran dari akad verbal ke ekspresi sosial umum; dari dialog religius ke tindakan fungsional; dari ruang transaksi simbolik ke platform digital; ketegangan antara konteks tradisional dan modern; serta munculnya kesadaran simbolik yang terfragmentasi. Studi ini memberikan kontribusi konseptual terhadap kajian living hadith dengan menyoroti adaptasinya dalam praktik ekonomi kontemporer. Selain itu, penelitian ini menawarkan wawasan penting mengenai upaya pelestarian dan artikulasi ulang nilai-nilai etika Islam di tengah budaya digital dan perilaku konsumtif yang terus berkembang.]